VIBRATION ANALYSIS OF THE TOOL BEARING SPINDLE IN CASE OF SUPERFINISHING TECHNOLOGIAL PROCESSES ESTABLISHMENT OF THE GENERAL MOVEMENT EQUATIONS - Popescu, Daniel (International Journal of Research -GRANTHAALAYAH, 2020)
The paper presents a mathematical model for determining the general movement equations that describe the vibration movement of the tool bearer spindle at superfinishing operations. There are presented the specific problems and the work schematics. The mathematical model uses the axioms of kinetic impulse and moment derivatives. At superfinishing, the spindle is eccentric and its working position is vertical. A series of simplifying assumptions are used, such as: Bernoulli’s hypothesis, the movement is without shocks, there are no remnant tensions, the strains are of elastic nature only. There are emphasized the components of the movement equations under restricted matrix form. The effect of transversal contraction and the torsion vibrations are neglected.